2018
DOI: 10.18332/tid/89976
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy eating habits among adolescent waterpipe smokers in Jordan: The Irbid-TRY

Abstract: INTRODUCTION The relationship between waterpipe smoking and eating habits among adolescents has not been investigated, thus the aim of the current study was to compare eating habits among adolescent cigarette-only, waterpipe-only, dual smokers versus non-smokers. We hypothesize that adolescent smokers practice unhealthy eating habits with worse habits among waterpipe smokers and dual smokers. METHODS Using a descriptive, cross-sectional design, self-reporting patterns of waterpipe, cigarette smoking and eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…Moreover, despite the increased consumption of milk and dairy products over time, less than half of adolescents reached the recommended intake of three servings per day [ 126 ]. Comparable findings were reported by different cross-sectional studies in Jordan, which also documented high consumption of sweetened beverages, sweets and chocolate, cakes and cookies, French fries, and potato chips [ 127 , 128 , 129 ]. Among adults and WRA, high consumption of salt was reported where the mean intake levels reached double the WHO recommendation of less than 5 g/day [ 126 ].…”
Section: Discussionsupporting
confidence: 42%
“…Moreover, despite the increased consumption of milk and dairy products over time, less than half of adolescents reached the recommended intake of three servings per day [ 126 ]. Comparable findings were reported by different cross-sectional studies in Jordan, which also documented high consumption of sweetened beverages, sweets and chocolate, cakes and cookies, French fries, and potato chips [ 127 , 128 , 129 ]. Among adults and WRA, high consumption of salt was reported where the mean intake levels reached double the WHO recommendation of less than 5 g/day [ 126 ].…”
Section: Discussionsupporting
confidence: 42%
“…In the present study of Lithuanian adolescents, an overwhelming majority (89.9%) of participants reported high consumption of fruits and vegetables; in contrast, studies of Portuguese and Italian schoolchildren found a less frequent consumption of these products [ 51 , 52 ]. However, we did find that high consumption of fruits and vegetables was significantly less common among currently smoking Lithuanian adolescents than among non-smokers, and this finding is in line with the results of other studies [ 53 , 54 ]. In the present study, we also found that 80% of Lithuanian adolescents reported a high consumption of sweets.…”
Section: Discussionsupporting
confidence: 93%
“…†: indicate all groups versus adolescents smoking Cg using one way ANOVA followed by LSD post-hoc comparisons oxidation-reduction equilibrium and CAT and GPx activities in adolescents smoking Wp or Cg versus never smokers. The results also confirm the harmful effect of dual smoking (Wp and Cg) on adolescent health (Alomari et al, 2020a;Alomari, Al-Sheyab, & Ward, 2018c;Alomari, Khabour, & Alzoubi, 2020b;Al-Sheyab & Alomari, 2018).…”
Section: Discussionsupporting
confidence: 68%
“…The data for this study are derived from a larger project, the Irbid-Try. The recruitment process that has previously been explained Alomari, Al-Sheyab, & Mokdad, 2020a;Al-Sheyab & Alomari, 2018), however, are briefly described herein.…”
Section: Participants and Designmentioning
confidence: 98%